Vascular inflammation on a chip: A scalable platform for trans-endothelial electrical resistance and immune cell migration - Ehlers, Haley; Nicolas, Arnaud; Schavemaker, Frederik; Heijmans, Jeroen P. M.; Bulst, Martin; Trietsch, Sebastiaan J.; van den Broek, Lenie J. (Frontiers in Immunology, 2023)
The vasculature system plays a critical role in inflammation processes in the body. Vascular inflammatory mechanisms are characterized by disruption of blood vessel wall permeability together with increased immune cell recruitment and migration. There is a critical need to develop models that fully recapitulate changes in vascular barrier permeability in response to inflammatory conditions. Here, we demonstrate a scalable platform for parallel measurements of trans epithelial electrical resistance in 64 perfused microfluidic HUVEC tubules under inflammatory conditions. The addition of inflammatory cytokines or human peripheral blood mononuclear cells affected barrier function and lead to changes in ICAM expression and endothelial morphology. We propose our platform as a powerful tool for modeling endothelial inflammation in combination with immune cell interaction that can be used to screen targets and drugs to treat chronic vascular inflammation.